Beyond individual factors: a critical ethnographic account of urban residential fire risks, experiences, and responses in single-room occupancy (SRO) housing - Catherine Liao; Colleen Varcoe; Helen Brown; Ian Pike (BMC, 2024)
Abstract Background Burn injuries are a significant public health concern, closely linked to housing conditions and socioeconomic status. Residents in socioeconomically deprived neighbourhoods are at increased risk of exposure to hazards due to older and poorer housing conditions and limited access to fire protection measures. Individual behaviours such as substance use, smoking, and hoarding are often highlighted as primary causes of residential fires, overshadowing the broader socioeconomic and structural factors that also play a significant role in housing safety. This paper explores the correlation between inadequate housing conditions and heightened fire risks leading to burn injuries, focusing on the contextual factors shaping everyday urban fire risks, experiences, and responses of residents living in Single-Room Occupancy (SRO) housing in Vancouver's Downtown East Side (DTES) and staff working in the fire, health, housing (social and private), and non-profit sectors. Methods As part of an ongoing ethnographic study, we partnered with the Vancouver Fire Rescue Services (VFRS) to conduct participant observations in private, non-profit, and government-owned SROs, modular homes, and a temporary shelter. This paper synthesizes insights from participant observations from the first author's self-reflexive journals, including informal conversations with approximately fifty-nine individuals such as SRO tenants, SRO managers/caretakers, health workers, burn survivors, municipal staff, not-for-profit staff, and firefighters. Results Urgent housing-related issues contributing to inequitable everyday urban fire risks were identified, such as structural deficiencies in SRO buildings and systems, inadequate waste management and storage, and inequitable approaches to addressing hoarding. Additionally, disparities in access to information and the interaction between interpersonal and structural stigmas were significant factors, underscoring the pressing need for intervention. Conclusion Communities like DTES, facing precarious housing conditions, disadvantaged neighbourhoods, and complex health and social challenges, necessitate a comprehensive and holistic approach to fire prevention and safety. Recognizing the interplay between housing instability, mental and physical health issues, unregulated toxic drug supply, drug criminalization, and structural inequities allows practitioners from various sectors to develop contextually driven fire prevention strategies. This multifaceted approach transcends individual-level behaviour change and is crucial for addressing the complex issues contributing to fire risks in underserved communities.